Optimalisasi Pengembangan UMKM melalui Pelatihan Pemasaran di Desa Jambu, Kecamatan Conggeang, Kabupaten Sumedang - Maudy Susanti; Mayang Indi Genousa; Tita Nursyamsiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Small and medium-sized enterprises (SMEs) play an significant part in national economic growth. In addition to playing a role in national economic growth and employment, small and medium-sized enterprises often play a role in sharing development results and are a driving force for growth in national economic activity. Marketing is an integral aspect of business management. Good management is important to enable the company to grow and develop better. Jambu Raya marketing which is one of the 2019 KKN-T programs of IPB University in Jambu Village, Conggeang District, Sumedang Regency. This program will help establish and grow small and medium-sized enterprises in Jambu Village. MSMEs are expected to improve their business quality and productivity, so that MSME products in Jambu Village can compete in a wider marketplace. Through this Champion Market program it is hoped that Jambu Village's UMKM will be able to improve the quality and productivity of its business, so that Jambu Village's UMKM products can compete in a broader market. This program consists of four activities including Product Development Class, Social Media Marketing Class, Account Creation, and Simple Bookkeeping. Key words: Champion market program, marketing, SMEs.